Identifying School Programs and Peer Roles in Juvenile Delinquency through a Mixed Method Approach - Kurniawan, Novian Candra; Khotimah, Khusnul; Efendi, Bintang Muhammad Sahara; Ni'matuzzuriyah, Ni'matuzzuriyah; Ruja, I Nyoman (Directorate of Research and Community Service, Universitas Negeri Yogyakarta, 2024)
Juvenile delinquency is something that violates the norms and rules that apply in the local area. Usually, the delinquency is caused by peers and lack of parental attention. This study aims to review students' knowledge and the influence of peers in committing juvenile delinquency. Then, this study also aims to find out the strategies and school programs in overcoming juvenile delinquency. Through a mix method explanatory approach, this research is expected to develop a comprehensive strategy in overcoming juvenile delinquency. In the first phase, this research uses quantitative methods by distributing questionnaires to 85 students as respondents which are then analyzed using SMART-PLS with structural equation model-partial least square (SEM-PLS) techniques. The second, qualitative phase conducted interviews with school principals, representatives of class teachers and counseling guidance teachers to get answers about school strategies in overcoming adolescent delinquency. Qualitative data was then analyzed thematically by compiling into program sections, sub-programs and descriptions. As a result, in direct testing, there are 2 accepted hypotheses: character-building competency against peer delinquency and delinquency behavior. However, peer delinquency does not have a positive and significant relationship with delinquency behavior. Indirect testing provided the finding that peer delinquency failed to mediate the relationship between character-building competency and delinquency behavior. Furthermore, based on the interviews conducted, a school program aims to overcome adolescent delinquency. The program involves internal and collaborates with external institutions such as KPAI, bhabinkamtibmas, and alumni who have achieved success. Then, the school also provides counseling on parenting by involving parents as participants. Thus, it can be seen that the school has taken a holistic and collaborative approach in dealing with juvenile delinquency. However, strong peer influence and lack of individual commitment may reduce its effectiveness.